Marketing Strategies for Education Services to Improving the Students Competitiveness of MAN I Aceh Barat - Muliadi, Riswan; Yusrianti, Susi; Bahri, Saiful (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to determine the marketing strategy of educational services in increasing the competitiveness of MAN I Aceh Barat with a descriptive qualitative approach through observation, interviews, and documentation. The research subjects included the head of the madrasah, the head of student affairs, teachers, students and the community. The results showed that the marketing strategy was carried out through four stages: planning (preparation of superior programs and needs-based services), organizing (formation of a promotion team, social media management, external cooperation), implementing (digital promotion, innovative activities, and participatory services), and supervising (periodic evaluation and monitoring of community response). The madrasah competitiveness model is measured through indicators such as increased student numbers, market share, institutional image, student satisfaction and loyalty, and value to stakeholders, reflecting the effectiveness of the marketing strategy and the madrasah's contribution to the community